Collective Reputation in Trade: Evidence from the Chinese Dairy Industry - Bai, Jie; Gazze, Ludovica; Wang, Yukun (The Review of Economics and Statistics, 2022)
The existence of collective reputation implies an important externality. Among firms trading internationally, quality shocks about one firm's products could affect the demand of other firms from the same origin country. We study such a reputation spillover in the context of a large-scale scandal that affected the Chinese dairy industry in 2008. Leveraging detailed firm-product level administrative data and official quality inspection reports, we document sizable reputation spillovers on uncontaminated firms. We further investigate potential mechanisms that could mediate the strength of collective reputation, including information accuracy, observability of the supply chain, and prior export experience.